Experimental study and simulation on the creep characteristics of machine-harvested seed cotton - Wei, Ximei; Zhang, Hongwen; Wang, Jun; Li, Shufeng; Wang, Lei; Du, Xintian (International Journal of Agricultural and Biological Engineering, 2024)
In view of the unclear understanding of the basic scientific problems such as the rheological mechanism of seed cotton, especially the lack of research on the creep characteristics of seed cotton, the machine-harvested seed cotton in the Xinjiang region was taken as the research object to find out the compression creep characteristics. The universal material testing machine was used to carry out a one-factor creep test, taking moisture content, feed quality, compression times, and trash content as test factors and instantaneous elastic modulus, hysteretic elastic modulus, viscosity coefficient, and delay time as test indicators. The ANOVA and correlation were analyzed by SPSS, and the creep process of the seed cotton was simulated by ADAMS. Results show that moisture content significantly affects the instantaneous elastic modulus, hysteretic elastic modulus, and viscosity coefficient (p<0.01). In addition, each value of which decreases with the increase in moisture content. Feed quality significantly affects the hysteretic elastic modulus and viscosity coefficient (p<0.05). Moreover, the hysteretic elastic modulus and viscosity coefficient increase with the increase in feed quality. The compression times significantly influence the instantaneous elastic modulus, hysteretic elastic modulus, and viscosity coefficient (p<0.01), each value of which increases with the increase of compression times. Furthermore, the trash content significantly influenced the hysteretic elastic modulus and viscosity coefficient (p<0.05). The absolute error between the simulated and experimental values ekis within −0.011-0.030 mm, and the relative error φk is less than 7%. The experimental results can provide theoretical and data support for the study of rheological characteristics of machine-harvested seed cotton, the design of seed cotton packing devices, and the molding quality of cotton bale (mold). Keywords: creep characteristics, machine-harvested seed cotton, analysis of ANOVA, one-factor tests, ADAMS DOI: 10.25165/j.ijabe.20241701.7705 Citation: Wei X M, Zhang H W, Wang J, Li S F, Wang L, Du X T. Experimental study and simulation on the creep characteristics of machine-harvested seed cotton. Int J Agric & Biol Eng, 2024; 17(1): 241-250.